Magnitude of a Metabolic Risk Profile in Sepsis Scales in Patients with Pneumonia (Global Journal of Medical Research, 2021)
Introduction: The mortality of community acquired pneumonia (CAP) ranges from 5% to 15%, depending logically on whether the study has been performed in the community or in a hospital setting, as well as varying also according to age. In Mexico as of June 26, 2021, there are 2,498,357 confirmed cases of COVID and 232,346 deaths. There are studies showing that cardiovascular disease is a risk factor for sepsis events. In the absence of a single prognostic marker, it is important to have clinical tools to estimate the probability of in-hospital death in septic patients and thus identify high-risk patients and improve the appropriate use of medical interventions to be performed. Objective: To know the magnitude of a metabolic risk profile in sepsis scales in patients with pneumonia.
Keywords: pneumonia; COVID 19; sepsis; prognostic scales